Mechanisms for the anti-obesity actions of bofutsushosan in high-fat diet-fed obese mice - Shinjiro Kobayashi; Yuki Kawasaki; Tatsuo Takahashi; Hironori Maeno; Masaaki Nomura (BMC, 2017)
Abstract Background The Kampo medicine bofutsushosan (BTS; Pulvis ledebouriellae compositae; Fang Feng Tong Sheng San) has been used as an anti-obesity treatment in overweight patients. In this study, we assessed the underlying physiological changes induced by BTS in obese mice maintained on a high-fat diet. Methods Male ICR mice were fed a 60% kcal fat diet for 5 weeks starting at 4 weeks of age and then fed the same diet with administration of water (control) or aqueous BTS extract (1.0-2.0 g/kg) for 25 days. Body weight, wet weight of isolated white adipose tissue, and obesity-related serum parameters (glucose, lipids, leptin, adiponectin) were measured after treatment. The mRNA expression levels of leptin, adiponectin, and UCP1 in the adipose tissues were determined by quantitative real-time polymerase chain reaction after the first 5 days of treatment. Results Bofutsushosan (1.5-2.0 g/kg) significantly decreased total body weight and total wet weight of white adipose tissue isolated from subcutaneous (retroperitoneal) and visceral regions (epididymal, mesenteric, and perirenal). At 2.0 g/kg, BTS also decreased total fat mass, visceral fat mass, and ratio of fat mass to body weight as measured by computed tomography, and significantly decreased epididymal adipocyte size after 14 and 25 days' treatment. Twenty-five days' treatment lowered serum glucose, insulin, leptin, and triglycerides, and reduced homeostasis model assessment-insulin resistance. Alternatively, 2.0 g/kg BTS significantly increased mRNA levels of adiponectin, leptin, and UCP1 in interscapular brown adipose tissue but not epididymal white adipose tissue after 5 days' administration. Conclusion In the early administration period, BTS increased mRNA expression levels of leptin, adiponectin, and UCP1 in brown adipose tissues. With longer administration, BTS improved insulin resistance, and subsequently reduced serum levels of leptin and triglyceride in parallel with decreased visceral white adipose tissue volume and adipocyte size.